Concordance between the academic faculty to which the student belongs with the vocational interests and the attributional styles of the causes that determined the admission to UNMSM in the selection process of year 2000 - Vicuña Peri, Luis Alberto (2001)
The present investigation tries on the agreement between the vocational interests and the School Professional Academic to which the student entered in the process of selection of the year2000. The evaluation of the interests was carried out by means of a questionnaire elaborated for the present study. The second used instrument evaluated the attributional styles. These tests were applied to an aleatory sample conformed by 20 academic schools of the nineteen Abilities with those that it counts the National University bigger than San Marcos requiring 698 examined with a level of trust of 95% and with an error of estimate of the 0.05. Of the total of having examined 22% communicate their desire to be changed specialty, without difference for the gender. The reasons of those who say that they will be changed they are the following ones: because it is not their vocation, because there is not work, and because the teaching is bad. The intention of the transfer goes toward human medicine, engineering of systems and right. Attributional style tends towards pessimism mainly by the tendency to self-responsibility very stable so that events do not depend on them directly, yet it is manageable. In sum, the transfers are promoted by vocation reasons, and the en trance to a different specialty it corresponds to their plan of life without they influence neither the gender neither the specialty to which was entered, discovery that makes necessary to implement the permanent service of counselling and vocational orientation.